Strategies for Tracking Anastasis, A Cell Survival Phenomenon that Reverses Apoptosis - Tang, Ho Lam (J Vis Exp, 2015)
Anastasis (Greek for “rising to life”) refers to the recovery of dying cells. Before these cells recover, they have passed through important checkpoints of apoptosis, including mitochondrial fragmentation, release of mitochondrial cytochrome c into the cytosol, activation of caspases, chromatin condensation, DNA damage, nuclear fragmentation, plasma membrane blebbing, cell shrinkage, cell surface exposure of phosphatidylserine, and formation of apoptotic bodies. Anastasis can occur when apoptotic stimuli are removed prior to death, thereby allowing dying cells to reverse apoptosis and potentially other death mechanisms. Therefore, anastasis appears to involve physiological healing processes that could also sustain damaged cells inappropriately. The functions and mechanisms of anastasis are still unclear, hampered in part by the limited tools for detecting past events after the recovery of apparently healthy cells. Strategies to detect anastasis will enable studies of the physiological mechanisms, the hazards of undead cells in disease pathology, and potential therapeutics to modulate anastasis. Here, we describe effective strategies using live cell microscopy and a mammalian caspase biosensor for identifying and tracking anastasis in mammalian cells.